Drucker on leadership new lessons from the father of modern management - Cohen, William A. 1937- (Jossey-Bass, 2010)
"A fresh look at vital lessons from "The Father of Modern Management"-exploring Peter Drucker's teachings on leadershipAs we approach what would have been his 100th birthday, the late Peter Drucker's management principles continue to be studied and applied by managers all over the world. Though many seek his lessons on the central element of management-leadership-he in fact wrote relatively little under this actual subject heading. Now, for the first time, William A. Cohen, a former student of Drucker's and a leadership expert and author in his own right, brings together Drucker's reflections on leadership, culled from his 40 books and hundreds of articles. Explaining why there is so little know about Drucker's ideas on leadership, this book is a must-read for students and fans alike looking to lead better in today's world"--Provided by publisher